2004
DOI: 10.1007/s00701-004-0344-y
|View full text |Cite
|
Sign up to set email alerts
|

An immunohistochemical study of extracellular matrix proteins laminin, fibronectin and type IV collagen in paediatric glioblastoma multiforme

Abstract: This study provides additional insights into tumour invasion features of paediatric GBM, as ECM plays a pivotal role in numerous cellular functions during normal and pathological processes. Although based on a limited number of patients, this investigation may serve as a challenge for the management of paediatric GBM, stimulating trials with larger patient numbers aimed at documenting specific factors influencing GBM prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 20 publications
0
15
0
1
Order By: Relevance
“…Several studies addressed the relation between fibronectin and tumors, including breast cancer, melanoma (30,31), and gliomas. Overexpression of fibronectin in glioblastoma as detected by immunohistochemistry was reported previously (32). The expression of fibronectin by glioma blood vessels suggests that this protein plays a role in the development of glioma vasculature (33).…”
Section: Discussionmentioning
confidence: 52%
“…Several studies addressed the relation between fibronectin and tumors, including breast cancer, melanoma (30,31), and gliomas. Overexpression of fibronectin in glioblastoma as detected by immunohistochemistry was reported previously (32). The expression of fibronectin by glioma blood vessels suggests that this protein plays a role in the development of glioma vasculature (33).…”
Section: Discussionmentioning
confidence: 52%
“…However, the nature of potential substrates and interactions of LOX with these substrates in the CNS is not known. In addition to collagen type I [11] and type IV [1], invasive astrocytes are known to aberrantly secrete a large amount of tropoelastin that becomes degraded without assembly [12]. Invasive astrocyte‐derived elastin, in addition to being a potential adhesive media, may provide unusually high local substrate concentration for LOX, resulting in increased generation of hydrogen peroxide, subsequent hydrogen peroxide‐mediated signalling and enhanced cell migration and invasion.…”
Section: Discussionmentioning
confidence: 99%
“…Components of the extracellular matrix (ECM) play a critical role during normal and pathological conditions in the central nervous system (CNS), including the development and invasion of primary brain tumours [1,2]. The invasive phenotype of astrocytes is a hallmark of tumour progression, but the molecular mechanisms that control the invasive cell behaviour, the role of the locally permissive ECM, and cell–ECM signalling in this matrix environment are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Glioblastomas are defined by an accumulation of several large ECM-components, i.e. collagens I, IV, VI, and fibronectin, laminin, versican, decorin, and tenascin-C [17,18]. It has been demonstrated that increasing concentrations of collagen I correlate positively with tumour invasiveness, but negatively with tumour growth.…”
Section: Discussionmentioning
confidence: 99%